Analysis of Impulsive Buying Among Generation Z and Millennials in Bekasi City: What is the Role of Flash Sales and Live Shopping? - Hidayah, Nanda Sari; Suhud, Usep; Febrilia, Ika (International Journal Of Education, Social Studies, And Management (IJESSM), 2025)
This study aims to explore the effect of flash sales, live shopping, and consumer trust on positive emotion in influencing impulsive buying behavior. This study uses a quantitative approach with data collected through questionnaires from 251 respondents who are Shopee e-commerce users in Bekasi City. Data analysis was carried out using the Structural Equation Modeling (SEM) method through AMOS software. The results showed that flash sales and live shopping have a positive and significant influence on impulsive buying and positive emotion. In addition, consumer trust was also found to play an important role in increasing positive emotion which in turn encourages impulsive buying behavior. These findings confirm that promotional factors and consumer trust play an important role in creating positive emotions that can trigger spontaneous purchase decisions on e-commerce platforms.